2007
DOI: 10.1089/ham.2007.1028
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Thrombosis at High Altitude Resulting in Loss of Limb

Abstract: Vascular thrombosis is an uncommon but recognized peril of high altitude travel. Traditionally, this has been associated with prolonged exposure to extreme altitudes where dehydration, hemoconcentration, cold, use of constrictive clothing, and enforced stasis due to severe weather have been named as contributing factors. It is widely hypothesized that hypoxia itself alters the coagulation cascade to create a prothrombotic milieu, though evidence thus far is limited and frequently conflicting. Case reports have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The exact underlying mechanism of this is not known but it is postulated to be multifactorial resulting from altered coagulation cascade, haematocrit values and platelet reactivity 1 2. Platelet adhesiveness and aggregation has been shown to be increased at HA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The exact underlying mechanism of this is not known but it is postulated to be multifactorial resulting from altered coagulation cascade, haematocrit values and platelet reactivity 1 2. Platelet adhesiveness and aggregation has been shown to be increased at HA.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet adhesiveness and aggregation has been shown to be increased at HA. In addition, hyperviscosity resulting from hypoxia mediated by increased red cell counts along with dehydration also increases the risk of thrombosis 1 2. Associated hereditary thrombophilic state may compound the above mentioned altered physiological state leading to an increased risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Veins that are noncompressible or that lack flow indicate the presence of a venous clot. Fagenholz et al (2007c) reported a case of arterial thrombosis at high altitude. They describe a previously healthy 41-year-old male hiking the Everest Base Camp trek with acute right lower extremity pain and loss of distal pulses.…”
Section: Vascularmentioning
confidence: 99%